Electrical solitons : theory, design, and applications - Ricketts, David Shawn; Ham, Donhee (Boca Raton, FL : CRC Press, 2011)
'This book details the physics, implementation, and dynamics of the electrical soliton, a unique nonlinear wave whose dynamics can be leveraged in many different high-speed electronics applications. After an overview of the soliton concept, the authors introduce the concept of the nonlinear transmission line, the medium on which electrical solitons are formed. Then they explain the unique dynamics of electrical solitons, including the many practical realities of solitons in lossy, non-ideal media. The mathematical background used to describe these phenomena is contained in the appendix, and fundamental physical concepts are presented so that the average engineering reader will understand'--
Includes bibliographical references and index.
Keywords: Solitons